Community‐Level Compact City Design, Health Care Provision, and Outcomes of Patients With Stroke - Yukihiro Imaoka; Nice Ren; Soshiro Ogata; Shogo Watanabe; Tomoya Itatani; Eri Kiyoshige; Hirotoshi Imamura; Kunihiro Nishimura; Syoji Kobashi; Yasuyuki Kaku; Koichi Arimura; Hitoshi Fukuda; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The optimal scale of urbanization for stroke health care provision and the potential impact of compact city design on stroke outcomes remain unclear. We investigated the impact of zip code area‐level compact city design using the walkability index (WI) and its mediators on stroke outcomes. Methods This nationwide retrospective study used data from patients with stroke from the J‐ASPECT study (2017–2022). WI was calculated as the average of 3 Z‐scored city design elements (population density, road connectivity, and variation in walkable facilities) from 113 1156 zip code areas in Japan. The association between WI and in‐hospital mortality, functional independence at discharge, and medical costs was assessed using multivariable mixed‐effects logistic regression model. Results Overall, 555 296 patients (median age, 75 [interquartile range, 66–83] years; female, 42.5%) from 818 hospitals were included. Higher WI was significantly associated with decreased in‐hospital mortality (odds ratio [OR], 0.94 [95% CI, 0.92–0.96]) and increased functional independence (OR, 1.03 [95% CI, 1.02–1.04]). The highest WI group was associated with decreased mortality, primarily mediated by management in intensive or stroke care units (proportion mediated, 0.46 [95% CI, 0.35–0.63]), and the highest WI group was associated with increased functional independence, mediated by short road distance to the hospital (proportion mediated, 0.30 [95% CI, 0.21–0.44]). Conclusions Zip code area‐level compact city design was associated with decreased in‐hospital mortality and increased functional independence. Compact city design at community level, even without large‐scale urbanization, may contribute to improving stroke care provision and outcomes in increasingly urbanized societies.